Delirium in the elderly: current problems with increasing geriatric age - Kukreja, Deepti (Indian J Med Res, 2015)
Delirium is an acute disorder of attention and cognition seen relatively commonly in people aged 65 yr or older. The prevalence is estimated to be between 11 and 42 per cent for elderly patients on medical wards. The prevalence is also high in nursing homes and long term care (LTC) facilities. The consequences of delirium could be significant such as an increase in mortality in the hospital, long-term cognitive decline, loss of autonomy and increased risk to be institutionalized. Despite being a common condition, it remains under-recognised, poorly understood and not adequately managed. Advanced age and dementia are the most important risk factors. Pain, dehydration, infections, stroke and metabolic disturbances, and surgery are the most common triggering factors. Delirium is preventable in a large proportion of cases and therefore, it is also important from a public health perspective for interventions to reduce further complications and the substantial costs associated with these. Since the aetiology is, in most cases, multfactorial, it is important to consider a multi-component approach to management, both pharmacological and non-pharmacological. Detection and treatment of triggering causes must have high priority in case of delirium. The aim of this review is to highlight the importance of delirium in the elderly population, given the increasing numbers of ageing people as well as increasing geriatric age.